THE LEVEL OF SOCIAL DISTANCE TOWARDS VISUALLY IMPAIRED PERSONS REGARDING TO OCCUPATION IN BOSNIA AND HERZEGOVINA - Amela Teskeredžić; Dženana Radžo Alibegović; Senada Salkić (Human Research in Rehabilitation, 2016)
The aim of this study was to determine the level of social distance towards visually impaired people in relation to the occupation of respondents. The study included 361 adult respondents from the territory of Bosnia and Herzegovina, and who had no personal, not professional contact with persons with impaired vision. For the purpose of this study was used scale of social distance (Oullette-Kuntz, Burge, Brown, Arsenault, 2010), which is adapted in terms of required statements and opinions of respondents to visually impaired people, rather than toward people with intellectual disabilities. For statistical analyzes were used methods of descriptive statistics, and methods of analysis of variance (ANOVA). All results of the study were conducted at a significance level of 0.05. The results indicate that there is no statistically significant difference in the opinions and level of social distance in relation to the occupation of respondents.